Analisis Kualitas Pelayanan Kesehatan dengan Kepuasan Pasien BPJS Kelas III di Instalasi Rawat Inap di Rumah Sakit Umum Daerah - Triana, Neni; Apriani, Maya; Darmansyah, M Ari (JURNAL KESEHATAN TERAPAN, 2025)
Satisfaction starts from the acceptance of patients from the first time they arrive, until the patient leaves the hospital. To achieve patient satisfaction, of course, by making efforts to provide quality health services in health institutions. The purpose of this study was to determine the relationship between physical evidence (tangible), responsiveness, reliability, assurance, and empathy with BPJS III patient satisfaction at the Inpatient Installation of Palembang Regional Hospital. The design of this study was an analytical survey with a cross-sectional study approach. The population is all BPJS III participant patients undergoing treatment at the Inpatient Installation of the RSUD totaling 485 people and samples were taken from September 2023 to February 2024 with a sample size of 83 respondents. The statistical analysis used was univariate, bivariate, and multivariate analysis to see the relationship between the quality of health services and the satisfaction of BPJS Class III patients at the Inpatient Installation of the RSUD. From the entire analysis process that has been carried out, it can be concluded that of the five independent variables, all variables are stated to have a simultaneous relationship with the satisfaction of BPJS Class III patients at the Inpatient Installation of the RSUD.